Yield and quality of soybean seeds inoculated with Bacillus subtilis strains - Tavanti, Tauan R. [UNESP]; Tavanti, Renan F. R. [UNESP]; Galindo, Fernando S. [UNESP]; Simões, Isadora [UNESP]; Dameto, Larissa S. [UNESP]; Sá, Marco E. De [UNESP] (Departamento de Engenharia Agrícola - UFCG, 2019)
The use of growth-promoting bacteria can increase the yield and quality of seeds of several annual crops, such as soybean. Based on that, the present study aimed to evaluate the effects of the inoculation of Bacillus subtilis strains on seed treatment, evaluating the yield and quality of seeds of two soybean cultivars. The experiment was conducted in a conventional system, in an Oxisol of clayey texture, in a crop under sprinkler irrigation. The experimental design was randomized blocks, arranged in split plots with four repetitions. Treatments were composed, in the plots, of two soybean cultivars: M7110 IPRO and Brasmax Desafio RR. Within the levels of subplots, the treatments consisted of inoculation and doses of inoculant: Bacillus subtilis Pant001 strain at doses of 0, 2, 3, 4 and 5 mL kg-1, and QST713 strain at the recommended dose of 2 mL kg-1. Inoculation with the strains Pant001 and QST713 increased the yield of both soybean cultivars tested, besides improving seed quality due to the increase in the concentration of total storage proteins, seedling emergence percentage and seed vigor by the accelerated aging test.

A utilização de bactérias promotoras de crescimento pode promover incrementos de produtividade e qualidade de sementes de diversas culturas anuais, como a soja. Com base no exposto, com o presente estudo objetivou-se avaliar os efeitos da inoculação de estirpes de Bacillus subtilis no tratamento de sementes avaliando-se a produtividade e qualidade de sementes de duas cultivares de soja. O experimento foi conduzido em sistema convencional, num Latossolo Vermelho Distrófico de textura argilosa, em cultivo irrigado por aspersão. O delineamento experimental utilizado foi em blocos ao acaso dispostos em parcelas subdivididas com quatro repetições. Os tratamentos foram compostos, nas parcelas, por duas cultivares de soja: M7110 IPRO e Brasmax Desafio RR. Dentro dos níveis de subparcelas, os tratamentos foram constituídos de inoculação e doses de inoculante: Bacillus subtilis estirpe Pant001 nas doses de 0, 2, 3, 4 e 5 mL kg-1, e estirpe QST713, na dose recomendada de 2 mL kg-1. A inoculação com as estirpes Pant001 e QST713 proporcionou incrementos de produtividade em ambas cultivares de soja testadas, além de melhorar a qualidade das sementes em função do aumento na concentração de proteínas totais de reserva, porcentagem de emergência de plântulas e vigor de sementes pelo teste de envelhecimento acelerado.
Produtividade e qualidade de sementes de soja inoculadas com estirpes de Bacillus subtilis
Keywords: Glycine max; plant growth-promoting bacteria; tetrazolium; storage proteins; seed vigor; Glycine max; bactérias promotoras de crescimento em plantas; tetrazólio; proteínas de reserva; vigor de sementes